Application of Recycle System on a Cocoa Pod Husks Gasification in a Fixed-Bed Downdraft Gasifier to Produce Low Tar Fuel Gas - Pranolo, Sunu Herwi; Waluyo, Joko; Prasetiyo, Jenni; Hanif, Muhammad Ibrahim (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
Biomass gasification is potentially generating not only producer gas but also tarry components. Practically, the gas may substitute traditional fuel in an internal combustion engine after reducing the tar. This research examined a producer gas recycle system to reduce tar component of producer gas generated with cocoa pod husks gasification using air as gasifying agent in a fixed-bed downdraft gasifier. Cocoa pod husks feed sizes were +1 sieve, -1+ 0.5 sieve, and -0.5 sieve. The gasification process was operated at the temperature range of 491 940oC and at various gasifying agent volumetric rates of 62.84; 125,68; and 188.53 NL/min or at equivalent ratio range of 0.014 0.042. A recycle system of outlet producer gas to gasifier was set at volumetric rates of 0.139; 0.196; and 0.240 L/min. The performance of the system was evaluated with analyzing the tar component using gravimetric method of ASTM D5068-13, and the gas component of CO, H2, CO2 and CH4 compositions in producer gas were analyzed using Gas Chromatography GC-2014 Shimadzu sensor TCD-14. This recycle system succeeded in reducing tar content as much as 97.19% at 0.139 L/min of recycle volumetric rate and at biomass feed size of -1+0.5 sieve. The producer gas contained CO, H2, CO2 and CH4 of 23.29%, 2.66%, 13.30%, and 14.18% respectively. The recycle system cold gas efficiency was observed 65.24% at gasifying agent volumetric rate of 188.53 L/min and at biomass feed size of +1 sieve.